Violence and legitimacy: the revolutions between 1827 and 1841 - Aljobín, Cristóbal (1996)
This article studies the relationship between political violence and liberal principles in Peru during the first decades of Republican government, 1827-1845. The logic of behavior of caudillos was immersed in a discourse of salvation of the Republic from corruption. This was the end in founding a stable government that looked over the national interest. In this way, the caudillos did not expect to build a de facto administration. They had as a goal to legitimize their administration through elections after a coup d'etat. In sum, this article analyzes the logic of behavior of the caudillos, and does not pretend to examine internal motives nor regional or class conflicts in each revolution.